MENGATASI HAMBATAN BELAJAR DALAM MATERI PLSV MENGGUNAKAN DESAIN DIDAKTIS DENGAN SCAFFOLDING DI SMP - Ari Ariansyah; Sugiatno Sugiatno; Bistari Bistari (Jurnal AlphaEuclidEdu, 2021)
This research aimed to determine how to overcome student learning barriers in the material of one-variable linear equations using didactical design with scaffolding in class VIII of SMP Negeri 4 Sungai Raya. The form of research used in this study was didactical design research. The data source of this study were students of class VIII B of SMP Negeri 4 Sungai Raya and the data were the initial and final test answer sheets and the results of interviews. The results showed that didactic design with scaffolding can overcome student learning barriers. Before being given a didactical design with scaffolding students were not able to made mathematical models in the form of story problems, students were not able to equivalent and classify similar terms, the incompatibility of the problem solving steps ordered by the completion steps done by students, students cannot solve the problem comes to the simplest form, and students made mistakes in calculating the value of a count operation. After being given a didactical design with scaffolding students have been able to make mathematical models in the form of story questions, students have been able to equivalent and classify similar terms, the problem solving steps ordered with the completion steps done by students are appropriate, students can already solve the problem to the simplest form, and students are able to calculate the value of a calculated operation correctly even though there are a few operating errors in some problems. Keywords: Didactical Design, Learning Obstacles, Scaffolding